PENEGAKAN HUKUM TERHADAP KEJAHATAN TRANSAKSI ELEKTRONIK DENGAN MENGGUNAKAN METODE PHISHING (Studi Putusan Nomor: 764/Pid.Sus/2022/PN Pbr) - Mujahid Hamd (Universitas Harapan Medan, 2025)
Phishing is a rapidly evolving crime that threatens the security of electronic transactions in Indonesia. This act involves deceptive methods aimed at illegally obtaining personal and financial information, typically by exploiting fraudulent emails or websites. From a legal perspective, phishing has the potential to undermine public trust in digital systems. Its impact is not only felt by individual victims but can also affect social stability and the integrity of the legal system as a whole. This research aims to analyze law enforcement and the legal regulations governing phishing, including provisions in the KUHP and the Electronic Information and Transactions Law (UU ITE). By examining Case Decision Number 764/Pid.Sus/2022/PN Pbr, this study identifies various challenges faced by law enforcement in implementing existing regulations. The research employs a normative legal approach with descriptive analysis, aiming to identify issues and provide recommendations to enhance the effectiveness of law enforcement. The findings are expected to contribute new insights for improving the legal system in Indonesia and strengthening oversight mechanisms to prevent the recurrence of phishing incidents in the future.